Le hasard de la preuve Apports et limites de l'économie expérimentale du développement - Favereau, Judith (Gouvernement en question(s), 2021)
With the creation in 2003 of the Abdul Latif Jameel Poverty Action Lab (J-PAL) at the Massachusetts Institute of Technology, the researchers Abhijit Banerjee, Esther Duflo and Sendil Mullainathan aimed to "transform research into action". Indeed, one of J-PAL's objectives is to provide evidence of the practical effectiveness of development aid programmes using an experimental method that mimics clinical trials in medicine. Then, the goal is for this evidence to be used by policymakers. The accumulation and use of this evidence in the political sphere would lead to what Banerjee and Duflo call "a quiet revolution," that is to say a world in which extreme poverty would be eradicated. But how are the results of these experiments produced? Do these experiments really enable evidence to be produced? Are the results of these experiments reliable and usable by policymakers? Can one transpose the results of an experiment from a specific territory to another one? Can such a method lead to a more profound transformation of anti-poverty policies? This book aims to answer these questions by conducting an epistemological analysis of J-PAL's approach. In doing so, this book explores the validity of the method promoted by J-PAL's researchers, as well as its significance and more general contribution to development economics and anti-poverty policies.